Gabapentin but not vigabatrin is effective in the treatment of acquired nystagmus in multiple sclerosis: how valid is the GABAergic hypothesis?. Issue 1 (1st July 2001) - Bandini, F; Castello, E; Mazzella, L; Mancardi, G L; Solaro, C
Abstract : Acquired nystagmus occurs frequently in patients with multiple sclerosis and is often the cause of illusory motion of the environment (oscillopsia), and blurring of vision. Based primarily on the beneficial effect of gabapentin on acquired pendular nystagmus (APN), a GABAergic mechanism in controlling nystagmus has been hypothesised. If increasing GABA concentrations in the CNS are critical for the treatment of nystagmus, then a selective GABAergic drug should be highly successful. However, as gabapentin is not a selective GABAergic agent, vigabatrin, a "pure" GABAergic medication, and gabapentin, were compared in a single blind cross over trial in eight patients with definite multiple sclerosis. Patients were randomly assigned to begin with gabapentin (1200 mg daily) or vigabatrin (2000 mg daily). Neuro-ophthalmological and electro-oculographic (EOG) evaluations were performed four and three times, respectively. Treatment efficacy was based on improving visual acuity and EOG indices (amplitude or frequency of nystagmus, or both) by at least 50% of pretreatment values. Three out of eight patients dropped out due to adverse effects. In the remaining five patients gabapentin improved symptomatic pendular or gaze evoked jerk nystagmus in four. Three patients decided to continue gabapentin therapy. Importantly, vigabatrin proved useful in only one out of five patients, suggesting that gabapentin effectiveness may be related to additional non-GABAergic mechanisms of action. Interaction with cerebral glutamate transmission by inhibition of NMDA receptor might be an alternative hypothesis for the therapeutic action of gabapentin.